Multicriteria Evaluation of Urban Regeneration Processes: An Application of PROMETHEE Method in Northern Italy - Bottero, Marta; Oppio, Alessandra; D’Alpaos, Chiara (Advances in Operations Research, 2018)
The paper illustrates the development of an evaluation model for supporting the decision-making process related to an urban regeneration intervention. In particular, the study proposes an original multi-methodological approach, which combines SWOT Analysis, Stakeholders Analysis and PROMETHEE method for the evaluation of alternative renewal strategies of an urban area in Northern Italy. The article also describes the work carried out within an experts’ panel that has been organized for validating the structuring of the decision problem and for evaluating the criteria of the model.